Validation and recognition of professional qualifications and competencies acquired abroad : criteria-based analysis of new and existing opportunities in Germany - Böse, Carolin [Verfasser]; Annen, Silvia [Verfasser] (My University, 2025)
“How can the recognition of foreign professional qualifications be improved and accelerated? This question remains a highly debated topic in German integration policy, especially given the ongoing skilled labor shortage. While the Federal Recognition Act has been the primary focus, two other legally established pathways exist for validating experience-based competencies. However, these methods have received less attention regarding individuals with competencies acquired abroad. This paper compares these three pathways in terms of standards, methods, stakeholders, and outcomes through a criteria-based document and literature review. The central research question asks: What differences exist between the procedures, and what implications do these differences have for utilizing the pathways, particularly for individuals with foreign-acquired competencies? Findings reveal similarities in various criteria but also significant differences, particularly in the entitlements conferred at the end of the process. This highlights the challenge of enhancing transparency and accessibility to promote recognition of informally and non-formally acquired competencies obtained abroad.“ (authors‘ abstract; BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; L 2.1.1 Informelles Lernen; 370; Auslandsqualifikation; Kompetenz; Anerkennungsgesetz; Externenprüfung; Informelle Kompetenz; Nicht-formale Qualifikation; Anerkennung